The cleavage of spike protein НА0→НА1/HA2 by trypsin permits activation of the M2 channel without its proteolytic cleavage in the influenza A virus - Zhirnov, Oleg P.; Chlanda, Petr (Virology, 2021)
M2 plays numerous regulatory roles in influenza A virus infection confirming the old adage: “a little body often harbors a great sense”. The comment here demonstrates that a small viral protein M2, having 14 kD m.w. and situating in the virion at a minor amount of only about 40 molecules per virus particle is resistant to trypsin at concentrations initiating the HA0 cleavage and virus infectivity activation. A mechanism involving a programmed disassembly by cascade-type transmembrane signaling of the HA-M2-M1-RNP cooperation during virus entry into the infected cell is proposed.
Gesehen am 26.07.2021